Modern situation in definition of the status of the Caspian Sea and the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The article deals with the present status of the Caspian sea. The author analyses in detail the basic issues and multilateral intergovernmentalagreements that regulate the activities on the sea and the adjacent areas. The classification of major principles is offered forthe readers. Possible future perspectives of development in this area are offered for the readers. Applicable regional aspects of the Lawof the sea are mentioned in the work. The article touches on the issues of the Caspian sea status. Some argreements in that field areconsidered in more detail. The positions of littoral countries is scrutinized as well.